2014
DOI: 10.1002/jsfa.6620
|View full text |Cite
|
Sign up to set email alerts
|

Onion extract (Allium cepaL.), quercetin and catechin up-regulate paraoxonase 1 activity with concomitant protection against low-density lipoprotein oxidation in male Wistar rats subjected to oxidative stress

Abstract: The findings may explain the anti-atherosclerotic effect of onion and also foods containing quercetin and catechins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Quercetin and, to a lesser extent, catechin induced similar effects [28]. In this animal model, the administration of Aronia melanocarpa juice statistically restored the PON activity of rats on a high-fructose and unsaturated fat diet [29].…”
Section: Plant Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin and, to a lesser extent, catechin induced similar effects [28]. In this animal model, the administration of Aronia melanocarpa juice statistically restored the PON activity of rats on a high-fructose and unsaturated fat diet [29].…”
Section: Plant Preparationsmentioning
confidence: 99%
“…In male Wistar rats receiving a 400 mg/kg dose of rutin for two weeks, the hepatic activity of PON1 increased by 17% compared to controls [60]. In this animal model, Jaiswal et al showed that administration of quercetin, and to a lesser extent catechin, significantly attenuated the adverse effects of HgCl 2 by upregulating PON1 activity and protected against LDL oxidation and lipid peroxidation [28]. A similar result was found by Mohammadshahi et al, who also observed a recovery in the decreased PON1 activity in arthritic rats when administering soy isoflavones (genistein and daidzein) for 50 days [33].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Different experimental models involving toxins or metabolic diseases ( i.e. , HgCl 2 toxicity [ 108 ], ethylene glycol-induced renal failure [ 109 ], streptozotocin-induced diabetic rats [ 110 ], Apoe -deficient mice [ 111 , 112 ] and cystathionine beta synthase-deficient mice [ 113 ]); catechins, alone or in combination with other polyphenols (quercetin) or foods (wine); or procyanidins (a group of flavonoids that are oligomeric forms of catechins present in red wine, grapes and apples) [ 110 ] have demonstrated up-regulation of PON1 levels or protective activity against LDL oxidation and lipid peroxidation. These studies raised important caveats such as the influence of the chemical nature of flavonoids or isoflavonoids, the experimental approach and selection of the animal model.…”
Section: Pon1 and Chemical Compounds Present In Mediterranean Dietmentioning
confidence: 99%
“…Medicinal plants such as Morus alba leaves extract [82], ginger [84], nuts [85], pumpkin [86], B-glucan [87], berry fruits [88], yellow onion (Allium cepa L.) [89] and resveratrol [90] have the capability to improve hypercholesterolemia by reducing total lipids, cholesterol and triglycerides. Many of the plants contain bioactive components having a potent antioxidant activity.…”
Section: Impact Of Phytotherapymentioning
confidence: 99%